2019
DOI: 10.1016/j.jaci.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Harmonized outcome measures for use in asthma patient registries and clinical practice

Abstract: Background: Asthma, a common chronic airway disorder, affects an estimated 25 million persons in the United States and 330 million persons worldwide. Although many asthma patient registries exist, the ability to link and compare data across registries is hindered by a lack of harmonization in the outcome measures collected by each registry. Objectives: The purpose of this project was to develop a minimum set of patient-and provider-relevant standardized outcome measures that could be collected in asthma patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…To help achieve this level of collaboration and data interoperability, a set of common demographic and clinical outcome measures were identified and adopted across all of the aforementioned research programs. The adoption of common data elements (CDEs) within these studies reduces the variability of data collection, and ultimately supports the secondary use of Brain-CODE data by facilitating the pooling of participant-level data across datasets (1,(3)(4)(5)(6). The primary objective of the present study was to use the CDEs to assess psychiatric comorbidity across various neurological diseases.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To help achieve this level of collaboration and data interoperability, a set of common demographic and clinical outcome measures were identified and adopted across all of the aforementioned research programs. The adoption of common data elements (CDEs) within these studies reduces the variability of data collection, and ultimately supports the secondary use of Brain-CODE data by facilitating the pooling of participant-level data across datasets (1,(3)(4)(5)(6). The primary objective of the present study was to use the CDEs to assess psychiatric comorbidity across various neurological diseases.…”
Section: Introductionmentioning
confidence: 97%
“…These data must be sufficiently comparable to allow meaningful data integration, and in the absence of common demographic variables and outcome measures it is difficult to pool data from different initiatives (2). Establishment up front of a minimum set of unambiguously defined and standardized assessments across initiatives will facilitate data sharing and integration and enable meaningful cross-initiative analyses (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes included current need for daily asthma controller medication, lifetime emergency room visit for asthma, and lifetime overnight hospitalization for asthma (Figure 1). Asthma-related medication use, emergency room visits, and hospitalizations are frequently studied asthma outcomes that reflect asthma severity, control, and healthcare utilization (28)(29)(30). While some studies have reported associations between particular air toxics and these asthma subphenotypes (9,11,12), none addressed our goal to identify combinations of air toxics from a large national assessment of air toxics associated with these asthma outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is one of the most common chronic pulmonary disorders, affecting more than 330 million people worldwide, but remains incurable despite decades of collective efforts to prevent, diagnose, and treat the disease in a timely manner (1). Current clinical guidelines recommend management of symptoms at best (2).…”
Section: Introductionmentioning
confidence: 99%